Caregiver Quality of Life with Tyrosinemia Type 1. Issue 3 (6th November 2017) - Campbell, Hailey; Singh, Rani H.; Hall, Eric; Ali, Nadia
Abstract: Tyrosinemia type I (HT1) is an inborn error of metabolism (IEM). Current management guidelines include lifelong specialized diet and use of the orphan drug, nitisinone. This study explores the quality of life (QOL) of caregivers of children with HT1. Caregivers for 26 children with HT1 completed a questionnaire (TYR‐QOL) adapted to this patient population from an existing validated QOL questionnaire (PKU‐QOL). Responses were analyzed via domain scores, based on predetermined scoring guidelines. Results suggest HT1 has a moderate overall impact on caregiver QOL, with emotional aspects of the disease having the greatest impact. HT1 diet and specialized formula also had an impact on caregiver QOL, with the vast majority feeling guilt if their child's diet and specialized formula plan were not followed. Management of nitisinone did not impact caregiver QOL. Results were compared to the phenylketonuria (PKU) population. Domain scores for the emotional, practical, social, and overall impact on QOL were higher for HT1 than for mild PKU, indicating a greater impact on QOL. Domain scores for practical and social aspects were similarly higher for HT1 than for classic PKU, though emotional and overall impacts were comparable. This is the first questionnaire to assess QOL in caregivers of children with HT1. Results can be used to better understand psychosocial implications of HT1 and assist healthcare professionals in addressing treatment issues.